Kecerdasan Emosional dan Kemampuan Mengajar Guru dalam Meningkatkan Kualitas Pengelolaan Kelas di Sekolah - Arizka Harisa; Ali Imran; Wildan Alwi (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2022)
This research aims to know and analyze about the emotional intelligence of teachers and teacher teaching ability which is associated with the quality of classroom management, allegedly the emotional intelligence of teachers and the ability to teach teachers has a relationship to the quality of classroom management in schools. For this reason, in this study using quantitative analysis to look for relationships between variables, research data was collected using questionnaires with a likert scale to teachers at the State High School (SMAN) in Ciputat South Tangerang. From research, it can be known that emotional intelligence has a relationship with improving the quality of classroom management, as well as the ability to teach teachers who have a relationship with efforts to improve the quality of classroom management in schools. In other words, efforts to improve the quality of class management at school in the implementation of the learning process can be done by the emotional intelligence in the teacher, and there is an increase in teaching ability owned by teachers, a teacher as a leader in the school class needs to have emotional intelligence and high teaching ability so that it will produce a quality learning process created by quality classroom management.